1995
DOI: 10.1159/000188480
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation with Low-Dose Immunoglobulins for Moderate IgA Nephropathy and Henoch-Schönlein Purpura

Abstract: Recently, our group has shown that a 3-month course of intravenous immunoglobulin (2 g/kg/monthly) followed by 6 months of intramuscular immunoglobulins (IMIG, 16.5%, 0.35 ml/kg every 15 days) was able to slow or to stop the decline in the glomerular filtration rate, to reduce proteinuria, hematuria, leukocyturia and the histological index of activity on renal biopsy in patients with severe forms of IgA nephropathy (IGAN) and Henoch-Schönlein purpura (HSP). The aim of this open prospective trial was to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 26 publications
(37 reference statements)
0
32
0
2
Order By: Relevance
“…It has been demonstrated that IgAN results in end-stage renal disease (ESRD) in 30–40% of individuals during a 20-year follow-up [2,3]. The progressive nature of this disease has prompted a search for novel treatments that are capable of preserving renal function; however, no specific treatment has yet been established [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that IgAN results in end-stage renal disease (ESRD) in 30–40% of individuals during a 20-year follow-up [2,3]. The progressive nature of this disease has prompted a search for novel treatments that are capable of preserving renal function; however, no specific treatment has yet been established [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…IVIg has also shown beneficial effects in patients with ANCA-associated vasculitis (AAV) refractory to standard therapy with prednisone and CyP [67]. In HSP, IVIg inhibited disease progression in isolated case reports [68,69].…”
Section: Intravenous Immunoglobulinmentioning
confidence: 99%
“…Recher et al (2010) reported a case report on unexpectedly successful a low-dose regimen (0,6 g/kg) in female patient with inclusion body myositis which costs approximately fourfold less than high-dose IVIG. In Henoch-Schönlein purpura some authors (Heldrich et al, 1993, Rostoker et al, 1995, Ruellan et al, 1997) administered low-dose or lower limit of high-dose regimens, others (Rostoker et al, 1994, Lamireau et al, 2001, Fagbemi et al, 2007 strictly apply 2 g/kg. Apart from the dose applied all authors emphasize dramatic improvement of IVIG treatment already after 24 hours after beginning (Girisgen et al, 2011).…”
Section: Conditionmentioning
confidence: 99%